Description of a new leaf litter toad of Leptobrachella (Anura, Megophryidae) from Hunan, China - Huang, Jie; Zhang, Fang-Peng; Jiang, Wan-Sheng; Tian, Yong-Xiang; Huang, Xing-Long; Xu, Ya-Lan; Liu, Jing; Li, Xin-Yu; Zhang, You-Xiang; Wu, Tao (Zoosystematics and Evolution, 2025)
A new leaf litter toad, Leptobrachella yongshunensis sp. nov. , is described on the basis of morphological, acoustic, and molecular data in this study. The new species was distributed in Xiaoxi National Nature Reserve, Yongshun County, Xiangxi Tujia and Miao Autonomous Prefecture, Hunan Province, China. Phylogenetical analysis revealed that the new species is sister species of L. wulingensis (p-distance 0.019 in 16s rRNA gene, p-distance 0.073 in COI gene). The duration of advertisement call was 194.2 ± 6.7 ms, the mean dominant frequency of the first note was 3.885 ± 0.066 kHz, and the mean dominant frequency of the second note was 3.914 ± 0.052 kHz. The new species can be distinguished from its congers by the following morphological characters: snout-vent length (SVL) 27.2–28.9 in males, SVL 26.2–31.6 in females; black spots on flanks; toes webbing rudimentarily; narrow fringes on toes; creamy white ventral body with indistinct black speckling at margins; dorsal body with sparse large warts, dense little wart grains, and longitudinal ridges; head width greater than head length; tibiotarsal articulation reaching to anterior edge of the eye; brick-red color in the dorsal surface; upper parts of iris bright coppery in life. We still supplemented the molecular data of the COI gene of L. wulingensis for further research. The discovery of the new species not only enhances the species diversity of the Wuling Mountains, but also suggests the hidden species diversity in the area.